2011
DOI: 10.3354/meps09283
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of larval abundance at hydrothermal vents on seamounts: evidence for recruitment limitation

Abstract: Because of their ephemeral nature and patchy distribution, hydrothermal vents on mid-ocean ridges are newly colonized by allochthonous larval sources after catastrophic eruptions, but their hydrothermal benthic invertebrate populations are maintained by local larval supply. In the present study, I examined spatial patterns of larval abundance and associated adult assemblages at hydrothermal vents on 3 seamounts each at the Mariana Arc and Kermadec-Tonga Arc. Because seamounts are topographically distinct featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Within a region, individual vent patches rarely host the full species pool . In some regions, neighboring vents may differ strikingly in species composition, as has been observed in the mid-Atlantic (Desbruyères et al, 2001) western Pacific (Podowski et al, 2010;Metaxas, 2011), and Gulf of California (Goffredi et al, 2017). In contrast, in the eastern Pacific, individual vents tend to host a subset of the province's species pool, without geographic clines (Juniper et al, 1990;Van Dover and Hessler, 1990).…”
Section: Vent Communities As Metacommunitiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Within a region, individual vent patches rarely host the full species pool . In some regions, neighboring vents may differ strikingly in species composition, as has been observed in the mid-Atlantic (Desbruyères et al, 2001) western Pacific (Podowski et al, 2010;Metaxas, 2011), and Gulf of California (Goffredi et al, 2017). In contrast, in the eastern Pacific, individual vents tend to host a subset of the province's species pool, without geographic clines (Juniper et al, 1990;Van Dover and Hessler, 1990).…”
Section: Vent Communities As Metacommunitiesmentioning
confidence: 93%
“…Consequently, in this setting, the role of larval swimming in larval transport is not clear. Observational studies have suggested that larval swimming toward the seafloor or induced passive sinking can be retentive, limiting dispersal distance, whereas modeling studies suggested that being near the seafloor rather than higher in the plume may actually increase dispersal, except when constrained by valley walls Metaxas, 2011;Mullineaux et al, 2013). Although there is some evidence to support the role of behavior in larval retention at vents, more research is necessary on this topic.…”
Section: Range Of Capabilities For Planktonic Dispersalmentioning
confidence: 95%
“…Locally, the sediment was covered with a thick, white microbial mat and the water above it was milky. Mean mussel cover was 18.7% (SD: 5.5%; n = 4; dive R1053; Metaxas ). The only evidence of predation was an eel attempting to feed on a mussel.…”
Section: Methodsmentioning
confidence: 99%
“…Vent communities can recover relatively rapidly from catastrophic natural disturbances (e.g., Tunnicliffe et al, 1997) because the larvae of many ventendemic taxa disperse widely (e.g., Marsh et al, 2001;Levin et al, 2016). However, recovery can also be slow where populations of chemoautrophic vent fauna depend on local source populations for their long-term maintenance in a region (Metaxas, 2011). For example, populations of the vent mussel G. gladius (one of the characterizing species of communities at vent habitats in the present study) appear to depend on a source population on Rumble V seamount (Boschen et al, 2015), which means that individual vent communities may be more vulnerable to disturbance than simple recovery models for vent communities predict.…”
Section: Relative Vulnerability Of Communities At Different Deep-sea mentioning
confidence: 99%